Sonatinas for piano - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Didenko, S. I. (Stanislav Iosifovich) (editor):::Contributor:::::::::::: (Moscow; Muzyka; Russia, 2025)
Collection containing the early sonatas, WoO 47, and "Sonatinas" WoO 51 and Anhang 5, no. 1, and the sonata, op. 49, no. 1, edited by S. I Didenko.